Combination of additional Spirulina platemsis and Curcuma longa supplements in diet and hormonal induction to improve reproduction performance of tinfoil barb Barbonymus schwanenfeldii (Bleeker, 1854) - Tuti Puji Lestari; Agus Oman Sudrajat; Tatag Budiardi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
The experiment was conducted in order to determine the role of each supplement combination of Spirulina platensis and Curcuma longa in the diet as well as the induction of Oodevto to tinfoil barb maturation and rematuration process. Randomized block design (RBD) with two factors consists of twelve treatments and five replicates of fish individuals was used. The dietary treatment comprises of four type, i.e. control diet, 3% kg-1 fish weight of turmeric supplementation in the diet, 3% kg-1 fish weight of spirulina supplementation in the diet; and the combination of turmeric and spirulina with 6% kg-1 supplementation in the diet. Meanwhile, the hormonal factor consists of three levels, i.e. 0.0 ml kg-1 fish weight, 0.25ml kg-1 fish weight (FW) and 0.50 ml kg-1 fish weight. We used sixty female broodstock with initial weight ranged 150-400 g and at stage II of gonad maturation. Fish were fed twice a day at 07.00 am and 05.00 pm at satiation level during 14 weeks. During the rearing period, gonado somatic index, maturation level, maturation period, 17 β estradiol concentration, eggs diameter and fecundity were observed. The result shows that all diet types which was combined with 0.50 ml kg-1 fish weight hormonal induction could improve reproductive performance up to 220%. This result comparatively higher than 0 ml kg-1 and 0.25 ml kg-1 hormonal inductions. Supplementation of 3% turmeric meal in the diet could produce 100% of mature broodstock out of season spawning. Thus, the combination of supplement either spirulina or tumeric with 0.5 ml kg-1 fish weight hormone induction can improve the induction maturation up to 2.2 times faster on the out-of- season spawning. Abstrak Penelitian ini dilakukan dengan tujuan untuk mengevaluasi peran kombinasi Spirulina platensis dan Curcuma longa dalam pakan dengan induksi Oodev terhadap proses pematangan gonad dan pematangan gonad kembali ikan tengadak. Metode yang digunakan adalah rancangan acak kelompok (RAK) dua faktor yang terdiri atas 12 kombinasi perlakuan dan 5 ulangan. Ulangan yang digunakan berupa ulangan individu. Faktor pakan terdiri atas empat jenis pakan yaitu pakan kontrol, pakan ditambah tepung kunyit 3% kg-1 bobot ikan, pakan ditambah tepung spirulina 3% kg-1 bobot ikan, dan kombinasi kunyit dengan tepung spirulina 6% kg-1 bobot ikan. Faktor hormon terdiri atas tiga taraf yaitu: 0,0 mL kg-1 bobot ikan, 0,25 mL kg-1 bobot ikan, dan 0,50 mL kg-1 bobot ikan. Ikan uji yang digunakan sebanyak 60 ekor ikan betina dengan bobot 150-400 g dan sudah mencapai tingkat kematangan gonad II. Ikan diberi pakan dua kali sehari (pagi dan sore) secara at satiation selama 14 minggu. Selama masa pemeliharaan parameter yang diamati meliputi indeks kematangan gonad, tingkat kematangan gonad, waktu pematangan gonad, konsentrasi 17β estradiol, diameter telur, dan fekunditas. Hasil penelitian menunjukkan bahwa semua jenis pakan yang dikombinasi dengan induksi hormon 0,50 mL kg-1 bobot ikan dapat meningkatkan kinerja reproduksi lebih baik (220%) dibandingkan induksi hormon 0,25 dan 0,0 mL kg-1 bobot ikan. Penambahan tepung kunyit 3% dalam pakan dapat menghasilkan induk matang 100% di luar musim pemijahan. Dengan demikian, pemberian kombinasi suplemen baik spirulina atau kunyit dengan induksi hormon 0,5 mL kg-1 bobot ikan dapat menginduksi 2,2 kali lebih cepat di luar musim pemijahan.